ANALISIS PENGUKURAN TINGKAT KEPUASAN PENGGUNA APLIKASI GOJEK KHUSUS DRIVER MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) DI SURAKARTA - Ananda, Angelica Terry; Susyanto, Teguh (STMIK Sinar Nusantara, 2025)
This study aims to analyze the level of user satisfaction among Gojek drivers in Surakarta by employing the End User Computing Satisfaction (EUCS) method. The research addresses various operational issues experienced by drivers, such as sudden performance drops, delayed Gopay balances, and missing customer addresses. The EUCS model evaluates satisfaction across five dimensions: content, accuracy, format, ease of use, and timeliness. Data was collected through questionnaires distributed to active Gojek drivers in Surakarta and analyzed using quantitative methods. The results indicate that all EUCS dimensions significantly influence user satisfaction, with each variable showing a positive and statistically significant relationship. These findings highlight the importance of continuous evaluation and improvement of the application to enhance driver satisfaction and operational efficiency. The study provides valuable insights for developers and management to prioritize feature enhancements and address user concerns, ensuring the sustainability and competitiveness of the Gojek platform. The research results show that the EUCS approach contributes positively to shaping user satisfaction of the Gojek Driver application.